2010
DOI: 10.1103/physrevlett.105.185001
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Magneto-Rayleigh-Taylor Instability Growth during the Implosion of Initially Solid Al Tubes Driven by the 20-MA, 100-ns Z Facility

Abstract: The first controlled experiments measuring the growth of the magneto-Rayleigh-Taylor instability in fast (∼100  ns) Z-pinch plasmas are reported. Sinusoidal perturbations on the surface of an initially solid Al tube (liner) with wavelengths of 25-400  μm were used to seed the instability. Radiographs with 15  μm resolution captured the evolution of the outer liner surface. Comparisons with numerical radiation magnetohydrodynamic simulations show remarkably good agreement down to 50  μm wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 17 publications
6
56
0
2
Order By: Relevance
“…As discussed above, the beryllium liners shown in red have an aspect ratio, A R ¼ R out /DR ¼ 6 for all simulations presented in this study. Numerical simulations 4 indicated and experiments [7][8][9][10][11] have confirmed that A R ¼ 6 liners should be sufficiently robust to the RT instability. These experiments were performed with drive currents of approximately 18 MA.…”
Section: Numerical Model Of Maglif Implosionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, the beryllium liners shown in red have an aspect ratio, A R ¼ R out /DR ¼ 6 for all simulations presented in this study. Numerical simulations 4 indicated and experiments [7][8][9][10][11] have confirmed that A R ¼ 6 liners should be sufficiently robust to the RT instability. These experiments were performed with drive currents of approximately 18 MA.…”
Section: Numerical Model Of Maglif Implosionsmentioning
confidence: 99%
“…The fuel preheating and the magnetically inhibited radial conduction reduce the required volume compression and thus the convergence needed to achieve fusion temperatures. Numerical simulations and experiments 4,[7][8][9][10][11] indicate thick walled liners with an aspect ratio (A R ¼ R outer /DR wall $ 6) should be adequately robust. Larger aspect ratios may be possible with the suppression of the electro-thermal instability, 12 but we use the conservative value A R ¼ 6 for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Code agreement was achieved only with the addition of an artificially azimuthally correlated initialisation. Good agreement between experiment and simulation was, however, achieved for MRT growth from a machined single mode perturbation, 11 suggesting that the poor agreement for randomly initialised liner implosions can be explained by enhanced levels of azimuthal correlation in the experiment over the simulation. This is a key because the MRT modes with the highest growth rate are fully azimuthally correlated.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the main thrust of this LDRD proposal was to study the key physics issue of liner stability. These experiments were extremely successful and resulted in several high-profile publications [6,7,8,9,10,11,12]. The results of these studies are summarized in Section 2.…”
Section: Introductionmentioning
confidence: 99%